2015
DOI: 10.5751/es-08023-200436
|View full text |Cite
|
Sign up to set email alerts
|

Effects of selective logging on large mammal populations in a remote indigenous territory in the northern Peruvian Amazon

Abstract: ABSTRACT. We examined the effects of selective timber logging carried out by local indigenous people in remote areas within indigenous territories on the mammal populations of the Yavari-Mirin River basin on the Peru-Brazil border. Recent findings show that habitat change in the study area is minimal, and any effect of logging activities on large mammal populations is highly likely to be the result of hunting associated with logging operations. We used hunting registers to estimate the monthly and yearly bioma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
0
5

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 34 publications
(31 citation statements)
references
References 39 publications
(42 reference statements)
0
24
0
5
Order By: Relevance
“…Hunting may reduce animal abundances in areas that experience the highest hunting rates, but these same areas may also represent favorable habitats for wildlife and continue to receive dispersing individuals from surrounding forests (Mayor et al . , Iwamura et al . ).…”
Section: Discussionmentioning
confidence: 99%
“…Hunting may reduce animal abundances in areas that experience the highest hunting rates, but these same areas may also represent favorable habitats for wildlife and continue to receive dispersing individuals from surrounding forests (Mayor et al . , Iwamura et al . ).…”
Section: Discussionmentioning
confidence: 99%
“…A factor that may have also influenced our findings could be the proximity of some fringe communities to the forest edge. During the study, it was observed that logged areas were closer to fringe communities and farms, making such areas more susceptible to human disturbances such as poaching [17,32]. Some of these differences in human and ecological variables may have influenced our findings.…”
Section: Discussionmentioning
confidence: 70%
“…These activities, when unchecked, may adversely affect several species, particularly canopy dwelling primates. Existing studies of the impact of anthropogenic forest disturbance on primate populations have provided valuable insights into (i) effects of selective logging on primate density [13][14][15][16][17][18]; (ii) the role of habitat disturbances in diet selection and primate abundance [14,19]; and (iii) behavioural and physiological responses of primates to habitat alteration [20,21]. In Ghana, no one has yet undertaken a quantitative assessment of the impacts of logging on primate abundance.…”
Section: Introductionmentioning
confidence: 99%
“…This may be a frequent threat in rural communities where wild animals are hunted for subsistence, because carcasses are handled with bare hands. Indeed, wildlife subsistence hunting in the Amazon region is a traditional source of food for rural populations (FitzGibbon 1998), and primates represent an important source of meat in the region (Puertas 2004; Bowler et al 2014; Mayor et al 2015). Furthermore, meat in these rural settings may be ingested raw or undercooked, and parasite pseudocysts and blood form trypomastigotes in the hunted animals could represent a high-risk of infection (Pereira et al 2009).…”
Section: Discussionmentioning
confidence: 99%